MicroRNA-221/222 Mediates ADSC-Exosome-Induced Cardioprotection Against Ischemia/Reperfusion by Targeting PUMA and ETS-1 - Lai, Tsai-Chun; Lee, Tzu-Lin; Chang, Yu-Chun; Chen, Yu-Chen; Lin, Shu-Rung; Lin, Shu-Wha; Pu, Chi-Ming; Tsai, Jaw-Shiun; Chen, Yuh-Lien (Frontiers in Cell and Developmental Biology, 2020)
Cardiovascular disease is a major health problem in industrialized and developing countries and is the leading cause of death and disability. Myocardial ischemia/reperfusion (I/R) causes damage to cardiomyocytes, such as apoptosis and hypertrophy. The purpose of this study was to investigate the effects of exosomes from adipose-derived stem cells (ADSC-Exo) on hearts from I/R mice and their underlying mechanisms. ADSC-Exo significantly decreased I/R-induced cardiomyocyte apoptosis and hypertrophy by TUNEL and WGA staining, respectively. Besides, the expression of apoptosis-related proteins, p-p53 and PUMA, and hypertrophic-associated proteins, ETS-1 and ANP were significantly reduced in cardiomyocytes of ADSC-Exo-treated I/R mice. Both PUMA and ETS-1 are reported to be as target genes for miR-221/222. I/R operation significantly reduced miR-221/222 expression, while ADSC-Exo treatment increased miR-221/222 expression by RT-qPCR. We also observed that cardiac I/R operation remarkably increased cell apoptosis and hypertrophy in miR-221/222 knockout (KO) mice, while ADSC-Exo reduced these effects of I/R operation. Furthermore, ADSC-Exo protected H9c2 cardiomyocytes from H2O2 treatment by reducing apoptosis and hypertrophy in vitro. H2O2-treated H9c2 cells significantly reduced miR-221/222 expression, while ADSC-Exo treatment reversed it. ADSC-Exo treatment decreased H2O2-induced PUMA and ETS-1 expression. Compared to control mice, I/R treatment significantly reduced p-AKT and increased p-p65, while ADSC-Exo and miR-221/222 mimics improved these effects. An AKT activator, SC79, and a p65 inhibitor, Bay 11-7082, reduced H2O2-induced cell apoptosis and hypertrophy. Based on these findings, ADSC-Exo prevents cardiac I/R injury through the miR-221/222/PUMA/ETS-1 pathway. Therefore, ADSC-Exo is a potent inhibitor of I/R-induced heart injury.